Conciliación, mediación y emociones : Una mirada para la solución de conflictos de familia. (2017)
Conciliation and mediation, as alternative dispute resolution mechanisms, incorporate the idea of interdisciplinarity as the new national and international trend in the search for non-violent solutions that are peace builders, for the solution of socio-legal conflicts. In particular for matters of family law because in these cases, especially, the feelings and emotions of the parties involved are implicated, which have deep psychological roots. Therefore, the current need for lawyers to be ethical, mediators, conciliators, and capable of integrating knowledge from different disciplines, to provide an integral solution to conflicts, especially those of family, given the important current relevance of this as a fundamental cell of society.